Using the Perseverance MEDA-RDS to identify and track dust devils and dust-lifting gust fronts - Toledo, D.; Apéstigue, V.; Martinez-Oter, J.; Franchi, F.; Serrano, F.; Yela, M.; de la Torre Juarez, M.; Rodriguez-Manfredi, J. A.; Arruego, I. (Frontiers in Astronomy and Space Sciences, 2023)
In the framework of the Europlanet 2024 Research Infrastructure (RI) Transnational Access (TA) programme, a terrestrial field campaign was conducted from 29 September to 6 October 2021 in Makgadikgadi Salt Pans (Botswana). The main goal of the campaign was to study in situ the impact of the dust devils in the observations made by the radiometer Radiation and Dust Sensor (RDS), which is part of the Mars Environmental Dynamics Analyzer (MEDA) instrument, on board NASA's Mars 2020 Perseverance rover. A number of dust devils and dust lifting by nonvortex wind gusts were detected with the RDS, and the different impacts of these events were analyzed in the observations. Dust devil diameter, advection velocity, and trajectory were derived from the RDS observations, and then panoramic videos of such events were used to validate these results. The instrument signal variations produced by the dust lifting (by vortices or wind gusts) in Makgadikgadi Pans are similar to those observed on Mars with the RDS, showing the potential of this location as a Martian dust devil analogue.